2014
DOI: 10.1603/an13100
|View full text |Cite
|
Sign up to set email alerts
|

Behavior, Development, and Predation of Podisus nigrispinus (Hemiptera: Pentatomidae) on Spodoptera frugiperda (Lepidoptera: Noctuidae) Fed Transgenic and Conventional Cotton Cultivars

Abstract: The association of insect-resistant plants with biological control is important in integrated management to reduce the density of pests below the economic injury level. The behavior, development, and prédation of Podisus nigrispinus (Dallas, 1851) (Heteroptera: Pentatomidae) were studied with the prey Spodoptera frugiperda (J, E. Smith, 1797) fed on the leaves of the cotton cultivars 'NuOpal' (transgenic), 'DeltaOpal,' 'EMX 910,' 'EMX 993,' or 'FMX 996' (conventional). The attraction of P. nigrispinus to S. fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
2
16
0
4
Order By: Relevance
“…However, the longevity of adults was significantly lower when compared to the longevity of the adults obtained in the direct effect experiment. [19] also observed a negative effect on longevity, reproduction and viability of P. nigrispinus when the predator fed on prey fed on Bt cotton plants. This low longevity in the indirect effect experiment was probably due to the food quality provided to the predators, since in the first case (direct effect) T. molitor pupae were offered, while in the second experiment (indirect effect) were offered S. frugiperda caterpillars fed on transgenic and no Bt cotton leaves were offered.…”
Section: Indirect Effect Of Bt Cotton and No Bt Cotton Plants On The mentioning
confidence: 89%
“…However, the longevity of adults was significantly lower when compared to the longevity of the adults obtained in the direct effect experiment. [19] also observed a negative effect on longevity, reproduction and viability of P. nigrispinus when the predator fed on prey fed on Bt cotton plants. This low longevity in the indirect effect experiment was probably due to the food quality provided to the predators, since in the first case (direct effect) T. molitor pupae were offered, while in the second experiment (indirect effect) were offered S. frugiperda caterpillars fed on transgenic and no Bt cotton leaves were offered.…”
Section: Indirect Effect Of Bt Cotton and No Bt Cotton Plants On The mentioning
confidence: 89%
“…The methodology proposed by Cruz (2000) with adjustments (Jesus et al, 2014) was used to obtain the S. frugiperda larvae. Briefly, male and female moths were maintained in polyvinyl chloride (PVC) tubes (10 cm diameter; 21.5 cm height) that were internally coated with bond paper sheets for egg laying and covered with voile at the top to prevent insect escape.…”
Section: Spodoptera Frugiperda Mass Rearingmentioning
confidence: 99%
“…Spodoptera frugiperda is a polyphagous species that infests cotton (Campos, Boiça-Júnior, Valério Filho, Campos, & Campos, 2012;Jesus, Boiça Junior, Alves, & Zanuncio, 2014), rice, millet, sorghum (Busato et al, 2004), soybean (Boiça Junior, Souza, Neves, Ribeiro, & Stout, 2015) and other crops. In Brazil, one of the factors that contribute to failures in the control of S. frugiperda is the large number of hosts caused by the succession of crops with different phenologies (Sá, Fonseca, Boregas, & Waquil, 2009;Barros, Torres, & Bueno, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Jesus et al (2014) observed that the predation of nymphs and adults, and the effects on the life cycle of the predator Podisus nigrispinus were higher on S. frugiperda larvae fed with NuOpal (Cry1Ac); however, the total viability of P. nigrispinus was lower when predating on S. frugiperda fed with NuOpal (transgenic cultivar). Spodoptera frugiperda acquires toxins from transgenic cotton, which can affect its natural predator P. nigrispinus.…”
Section: Natural Enemiesmentioning
confidence: 99%